Sorbus alnifolia protects dopaminergic neurodegeneration in Caenorhabditis elegans - Se-Myeong Cheon; Insoo Jang; Myon-Hee Lee; Dae Keun Kim; Hoon Jeon; Dong Seok Cha (Taylor & Francis Group, 2017)
Context: The twigs of Sorbus alnifolia (Sieb. et Zucc.) K. Koch (Rosaceae) have been used to treat neurological disorders as a traditional medicine in Korea. However, there are limited data describing the efficacy of S. alnifolia in Parkinson's disease (PD). Objective: This study was conducted to identify the protective effects of the methanol extracts of S. alnifolia (MESA) on the dopaminergic (DA) neurodegeneration in Caenorhabditis elegans. Materials and methods: To test the neuroprotective action of MESA, viability assay was performed after 48 h exposure to 1-methyl-4-phenylpyridine (MMP+) in PC12 cells and C. elegans (400 μM and 2 mM of MMP+, respectively). Fluorescence intensity was quantified using transgenic mutants such as BZ555 (Pdat-1::GFP) and and UA57 (Pdat-1::GFP and Pdat-1::CAT-2) to determine MESA's effects on DA neurodegeneration in C. elegans. Aggregation of α-synuclein was observed using NL5901 strain (unc-54p::α-synuclein::YFP). MESA's protective effects on the DA neuronal functions were examined by food-sensing assay. Lifespan assay was conducted to test the effects of MESA on the longevity. Results: MESA restored MPP+-induced loss of viability in both PC12 cells and C. elegans (85.8% and 54.9%, respectively). In C. elegans, MESA provided protection against chemically and genetically-induced DA neurodegeneration, respectively. Moreover, food-sensing functions were increased 58.4% by MESA in the DA neuron degraded worms. MESA also prolonged the average lifespan by 25.6%. However, MESA failed to alter α-synuclein aggregation. Discussion and conclusions: These results revealed that MESA protects DA neurodegeneration and recovers diminished DA neuronal functions, thereby can be a valuable candidate for the treatment of PD.